Chilling‐responsive DEMETER‐LIKE DNA demethylase mediates in poplar bud break. (30th August 2017) - Conde, Daniel; Le Gac, Anne‐Laure; Perales, Mariano; Dervinis, Christopher; Kirst, Matias; Maury, Stéphane; González‐Melendi, Pablo; Allona, Isabel
Abstract: Annual dormancy‐growth cycle is a developmental and physiological process essential for the survival of deciduous trees in temperate and boreal forests. Seasonal control of shoot growth in woody perennials requires specific genetic programmes responding to environmental signals. The environmental‐controlled mechanisms that regulate the shift between winter dormancy and the growth‐promoting genetic programmes are still unknown. Here, we show that dynamics in genomic DNA methylation levels are involved in the regulation of dormancy‐growth cycle in poplar. The reactivation of growth in the apical shoot during bud break process in spring is preceded by a progressive reduction of genomic DNA methylation in apex tissue. The induction in apex tissue of a chilling‐dependent poplar DEMETER‐LIKE 10 ( PtaDML10 ) DNA demethylase precedes shoot growth reactivation. Transgenic poplars showing downregulation of PtaDML8/10 caused delayed bud break. Genome‐wide transcriptome and methylome analysis and data mining revealed that the gene targets of DEMETER‐LIKE‐dependent DNA demethylation are genetically associated with bud break. These data point to a chilling‐dependent DEMETER‐like DNA demethylase mechanisms being involved in the shift from winter dormancy to a condition that precedes shoot apical vegetative growth in poplar. Abstract : Perennial plants, in temperate and boreal regions, need environmental sensitive molecular switches to shift between winter dormancy to a growth‐promoting genetic programme. This work reveals the crosstalk between DEMETER mediated DNA demethylation, resetting of cellular metabolism and regulation of shoot apical growth during poplar bud break.